Perbandingan Fungsi Ginjal dan Parameter Klinis pada Ibu Hamil Primipara dan Multipara dengan Preeklamsia Berat - Banjarnahor , Dharma Putra; Siahaan, Salmon Charles Pardomuan Tua Siahaan; Idarto , Areta; Yuwono , Natalia; Suryadarma , Antonius Yansen (Jurnal Kedokteran Meditek, 2026)
Introduction: Repeated pregnancies (multiparity) can result in cumulative physiological changes that adversely affect maternal kidney function, notably through increased risk of recurrent preeclampsia, which may contribute to long-term renal impairment. This study provides a comparative analysis of kidney function parameters between primiparous and multiparous pregnant women, focusing on how glomerular filtration rate (GFR) relates to other clinical indicators. Since current data on how multiparity impacts renal function are limited, this research addresses that gap. Purpose: The study aims to compare renal function parameters in primiparous versus multiparous pregnant women and assess the direction and strength of associations between GFR and key clinical variables. Methods: This quantitative cross-sectional study involved primiparous and multiparous pregnant women (n = 100) during routine examinations at Hospital X between January 3 and July 2025. Clinical data included age, body weight, hemoglobin, leukocytes, blood urea nitrogen (BUN), serum creatinine (SCr), and GFR (estimated by the Cockcroft–Gault formula). Statistical analyses compared groups and used correlation coefficients to quantify the direction and strength of relationships between GFR and clinical variables. Results: Primiparous and multiparous groups differed significantly in age, body weight, SCr, and GFR (p < 0.05). Multiparous women were older and had higher SCr, while primiparous women had higher body weight and GFR. GFR showed a positive correlation with body weight (r > 0, p < 0.05) and a negative correlation with age and SCr (r < 0, p < 0.05). SCr positively correlated with both BUN and body weight (r > 0, p < 0.05). Conclusion: Multiparity is associated with modest declines in kidney function, reflected by higher SCr and lower GFR relative to primiparous women. These findings underscore the need for early assessment and ongoing renal monitoring in multiparous mothers to help prevent nephrological complications and optimize clinical care throughout pregnancy.